(untitled) (Journal of Biomedical Investigation, 2011)
A prospective study to find out the prevalence of jaundice and acute pancreatitis was carried out in Nnamdi Azikiwe University Teaching Hospital Nnewi. The study period was from March 2009 to May 2009.Prior to the study, baseline determinations of serum alpha amylase and bilirubin levels were obtained. A total of 75 HIV seropositive patients were studied. 50 (66.7%) of these subjects had been on the first-line HAART drugs (such as Nevirapine, Didanosine and Tenofovir) for more than two years. None were on second line drugs. 25 out of the 75 HIV positive patients (33.3%) were not on anti-retroviral therapy at all (pre HAART). 25 HIV-seronegative individuals were used as controls in this study. 50 (66.7%) of the75 were females while 25 (33.3%) were males. Only 5(6.7%) were aged above 50. HIV screening was carried out for all the subjects studied using Determine Stat Pak and Unigold in accordance with the current national serial algorithm. Serum alpha-amylase assay was carried out for the 75 HIV patients using fully automated VITRO’S 350 analyser. 3 subjects (4%) had acute pancreatitis. Also, serum total and conjugated bilirubin assay were performed manually using Van den Bergh diazo reaction and only 1 patient (1.33%) had elevated plasma bilirubin level (jaundice). The CD4 counts of these subjects were evaluated using cyflow SL-3 Flowcytometer and 39 patients (52%) had their CD4 count greater than 200 while 36 patients (48%) had their CD4 count less than 200.